PREVALENCE AND INTENSITY INFECTION OF STRONGYLOIDES RANSOMI WORMS IN PIGS SLAUGHTERED AT PESANGGARAN SLAUGHTER HOUSE DENPASAR CITY - Akbar, Muhammad Wilmar; Suratma, Nyoman Adi; Oka, Ida Bagus Made (Buletin Veteriner Udayana, 2022)
This study aims to determine the prevalence and intensity of S trongyloides ransomi infections in pigs that were slaughtered at Pesanggaran animal slaughter house in Denpasar city. This study used 200 samples of pig feces. Stool samples are examined to determine the prevalence of infection using the floating method while the intensity of the infection determined using the Mc. Master method. The data obtained were presented descriptively. The results showed that the prevalence of S . ransomi infections was 5% with the intensity of infection was found that less than 500 eggs per gram of feces, it were categorized as having only mild infections.